Rancang Bangun Trainer Pengendalian Kecepatan Motor Listrik Menggunakan Inverter VFD (Variable Frequency Drive) - Fatma, Mira Wellya; Saputra, Georgi Beni; Arnella, Ami Juwita (CV. Information Technology Training Center - Indonesia (ITTC), 2026)
The lack of safe, integrated, and adequate VFD learning media in vocational education laboratories creates a significant gap between theoretical understanding and practical competence in induction motor control. This study aims to design, construct, and test a three-phase induction motor speed control trainer based on a VFD inverter suitable for Power Electronics practicum. The research employs a Research and Development approach grounded in experimental engineering, encompassing system design (block diagram, flowchart, wiring diagram), physical construction on a transparent acrylic panel equipped with MCB, contactor, push buttons, AT1 1.5 kW VFD, and 1 HP motor, and empirical testing across eight frequency points from 0 to 65 Hz under no-load conditions. Response variables include motor speed (RPM), phase current, phase voltage, and PWM output waveform. Results show a strong linear relationship between frequency and motor speed (R² = 0.998), with 3000 RPM achieved at 50 Hz consistent with synchronous speed theory. Operating current remains stable (0.26-0.36 A), the protection system functions fully, and the output waveform exhibits representative PWM characteristics. The trainer is proven to meet both technical and pedagogical feasibility criteria as an integrated learning medium that combines active safety, transparent visualization, and multivariable validation.